The True Results of the 2004 Philippine Presidential Election Based on the NAMFREL Tally - Verzola, Roberto (Kasarinlan: Philippine Journal of Third World Studies; Vol 19 No 2 (2004): Electoral Politics 1, 2007)
The National Citizens Movement for Free Elections (NAMFREL) tally of the 2004 Philippine presidential election shows clear signs of manipulation through selective tabulation in favor of Gloria Macapagal Arroyo, making her lead over Fernando Poe Jr. appear to be larger. However, much of the skew in the NAMFREL data can be removed by making certain corrective assumptions to estimate how the uncounted votes went. This paper asserts that during the 2004 Philippine presidential election, Gloria Macapagal Arroyo did not win by around 1.1 million votes over Fernando Poe Jr. It was a very close contest, with the most probable results ranging from a GMA win of around 156,000 votes or less, to an FPJ win of around 84,000 votes or less.
Keywords: presidential election; Philippines; NAMFREL; Fernando Poe Jr; Gloria Macapagal Arroyo